The Internal Organization and Supervision as Vital Issues in Post-War County Administration in Poland - Kamila Kędzierska (Journal on European History of Law)
In the article the matters of internal organization and supervision issues in post-war county administration in Poland are discussed on the example of Krakow County. In the first part statutes that dealt with the practical matters such as mail circulation, storing and marking the official documents are discussed. Author underlines their importance in relation to functioning of administrative offices. Next the matter of the provisions concerning handling of confidential correspondence such as internal order of the Krakow starosta issued on April 17th 1945 is discussed. The second part of the article is focused on the supervision and approval of developed documents. Author points out that internal decree number 15 issued on 26th of March 1945 was the first regulation about internal supervision. In this decree matters such as time schedules for delivering of official documents and meetings with starosta were regulated. Author’s conclusion is that provisions, that today seem natural for administration, were introduced to the newly created administration, which did not exist during the war and occupation, therefore they were crucial for the proper functioning of the county office.